2002
DOI: 10.1524/ract.2002.90.7_2002.399
|View full text |Cite
|
Sign up to set email alerts
|

Contrary effects of the water radiolysis product H2O2upon th dissolution of nuclear fuel in natural ground water and deionized water

Abstract: Radiolysis of water is a phenomenon which alters the prevailing conditions in the nearfield of a final geological repository for high-level nuclear waste (HLW), because the nominally anoxic conditions in the repository may change due to the production of oxidants close to the solidliquid interface of the fuel, caused by the alpha radiolysis of water.The influence of water chemistry and oxidant concentration in the liquid phase was tested by experiments which simulate chemical radiolysis effects. Leaching exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
65
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 17 publications
5
65
0
Order By: Relevance
“…Initially metaschoepite was formed, but was then replaced by studtite over a 2-year period. When investigating the surface evolution of UO 2 , Hanson et al [11] found that metaschoepite (UO 3 x 1-2H 2 O) is formed upon oxidation by O 2 , whereas leaching in H 2 O 2 leads to the formation of studtite (UO 4 x 4H 2 O), when the H 2 O 2 concentration is sufficiently high [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Initially metaschoepite was formed, but was then replaced by studtite over a 2-year period. When investigating the surface evolution of UO 2 , Hanson et al [11] found that metaschoepite (UO 3 x 1-2H 2 O) is formed upon oxidation by O 2 , whereas leaching in H 2 O 2 leads to the formation of studtite (UO 4 x 4H 2 O), when the H 2 O 2 concentration is sufficiently high [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…, and studtite, (UO 2 )O 2 (H 2 O) 4 , are the two only known minerals containing peroxide. Metastudtite is the main natural peroxide mineral (1) due to the irreversible dehydration of studtite (2).…”
mentioning
confidence: 99%
“…Metastudtite is the main natural peroxide mineral (1) due to the irreversible dehydration of studtite (2). Both these phases may be found in spent nuclear fuel exposed to water (3)(4)(5). Burns et al (6), by single crystal diffraction of a natural sample, determined the crystal structure of studtite to be monoclinic with space group C2/c.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we propose to investigate the effect of molecular species produced by 4 proposed a reduction mechanism based on radical interactions with the oxidized U(VI) released into solution.…”
Section: Introductionmentioning
confidence: 99%